Winning Spelling Bee Competition: The Representation of Black Girl in Akeelah and The Bee (2006) Movie - Hananto, Fiska Nur (Universitas Sebelas Maret, 2021)
This research examines the representations of African-American stereotype and the struggle of Black American girl in National Spelling Bee contest in Hollywood movie entitled Akeelah and the Bee (2006). The use of African-American English (AAVE) is one of the stereotype often depicted in Hollywood movie. Race theories are used to examine the relationship between race, racism and power. Meanwhile, Roland Barthes’s theory and semiotic film theory are used to examine the meaning portrayed in the movie. Findings show that the representation of Akeelah as a successful participant in the spelling bee competition challenges the stereotype of African American as academic underclass, and as associated with crime, failure and frustration. Akeelah is represented as a successful African American girl as she assimilates (adopts) American values of change/mobility, time and its importance, action and work orientation. The assimilation is achieved through a mentoring process and support from African American community.